Intrinsic movement variability at work. How long is the path from motor control to design engineering?. (March 2016) - Gaudez, C.; Gilles, M.A.; Savin, J.
Abstract: For several years, increasing numbers of studies have highlighted the existence of movement variability. Before that, it was neglected in movement analysis and it is still almost completely ignored in workstation design. This article reviews motor control theories and factors influencing movement execution, and indicates how intrinsic movement variability is part of task completion. These background clarifications should help ergonomists and workstation designers to gain a better understanding of these concepts, which can then be used to improve design tools. We also question which techniques - kinematics, kinetics or muscular activity – and descriptors are most appropriate for describing intrinsic movement variability and for integration into design tools. By this way, simulations generated by designers for workstation design should be closer to the real movements performed by workers. This review emphasises the complexity of identifying, describing and processing intrinsic movement variability in occupational activities. Highlights: Intrinsic movement variability is an essential feature of human motion. Motor control theories can explain the existence of intrinsic movement variability. Task and personal characteristics influence intrinsic movement variability. Intrinsic movement variability should be taken into account in workstation design.